Implikasi Yuridis terhadap Hak Keperdataan Anak yang Dilahirkan melalui Surrogate Mother (Ibu Pengganti) - Syifa Urradhiah; Rahmida Erliyani (Lembaga Yasin AlSys, 2026)
Although the practice of surrogate mother has received attention in various previous studies, research that specifically discusses the juridical implications for children’s civil rights and the limits of notarial authority in preparing deeds related to this practice remains limited. This study aims to analyze the construction of the legal relationship between children born through surrogate mother and the surrogate mother under the Indonesian legal system and to analyze the limits of notarial authority in preparing deeds related to the civil rights of children born through surrogate mother. This study used a qualitative approach with a doctrinal research design through primary and secondary legal materials collected through library research. Data were analyzed normatively and qualitatively using legal interpretation methods and analogical argumentation (argumentum per analogiam). The results showed that children born through surrogate mother have a legal relationship with the surrogate mother who gives birth to them based on an analogical construction of Article 43 paragraph (1) of the Marriage Law, reinforced by the principle of mater semper certa est and the theory of legal relationships. A surrogate mother agreement is declared null and void by law because it does not meet the objective requirements of Article 1320 of the Indonesian Civil Code, so all civil rights of the child are attached to the surrogate mother. The limits of notarial authority are determined by the existence or absence of a legal relationship recognized under Indonesian positive law. The conclusion of this study affirms the importance of legal certainty for children born through surrogate mother and the need for specific regulation of this practice. The implications of this study include theoretical contributions to the development of civil law and notarial law literature, as well as practical implications for notaries in applying the principle of prudence and refusing to prepare deeds intended to unlawfully transfer a child’s civil relationship.